AUDIT FIRM PERFORMANCE MANAGEMENT CONTRIBUTION TO AUDITOR’S ETHICAL DECISION MAKING IN DEALING WITH DYSFUNCTIONAL CLIENT - Prastiti, Alya Rizky; Gruben, Frank (Diponegoro Journal of Accounting, 2021)
The work environment of the auditors has a significant influence on the ethical decisions made. the reflection of the auditors’ performance is directly proportional to the environment that forms their skepticism as well as the leader who leads them. The author wants to reveal how performance management in an audit firm contribute to auditor’s ethical decision making. Furthermore, the author uses the literature review from reliable journals as evidence of the statement to describe the ideas and issues in this study.The findings in this thesis contribute to providing suggestions for audit team leaders in improving firm’s performance management in contributing to auditors’ ethical decision-making.